Study of Cysteine-Rich Protein 61 Genetic Polymorphism in Predisposition to Fracture Nonunion: A Case Control. (10th December 2015) - Ali, Sabir; Hussain, Syed Rizwan; Singh, Ajai; Kumar, Vineet; Walliullah, Shah; Rizvi, Nazia; Yadav, Manish; Ahmad, Mohammad Kaleem; Mahdi, Abbas Ali
Abstract : Background . Many factors are responsible for this impaired healing, especially in long bones, but a possible genetic predisposition for the development of this complication remains unknown till now. In the present study, we aim to examine the CYR61 gene polymorphism in fracture nonunion patients and the correlation with clinical findings. Materials and Methods . We performed SNP analysis of the CYR61 gene in 250 fracture nonunion patients and 250 healthy subjects were genotyped in this hospital-based case control study, and 56 cases were further evaluated for mRNA expression of CYR61 by real-time quantitative reverse-transcription PCR. Results . CYR61 gene TT, TG, and GG genotype frequencies of total fracture nonunion cases were 41.6%, 49.2%, and 9.20% and 54.4%, 39.2%, and 6.40% in healthy controls. Heterozygous TG genotype was found statistically significant in fracture nonunion cases compared with that in controls, whereas homozygous mutant GG genotype was not found significant. Moreover, we found that TG + GG genotypes were significantly different in serum expression of CYR61 mRNA when compared with cases (TT genotypes). Conclusions . Our result signifies that genotype of CYR61 affects the mRNA expression and acts as a risk factor that could synergistically increase the susceptibility of a patient to develop fracture nonunion.